GESTO E METÁFORA NO CINEMA: Uma análise cognitiva de Boi de Lágrimas de Frederico Machado - NOGUEIRA, Laís de Paula Freitas Carvalhêdo (2025)
This dissertation aims to investigate gestural language in cinema in articulation with other cinematographic elements such as setting and framing, focusing on its capacity to construct metaphorical meanings. To this end, it is grounded in the assumptions of Cognitive Linguistics, especially the theories of conceptual metaphor by Lakoff and Johnson (1980) and Kövecses (2010), and embodied cognition, which emphasize the centrality of bodily experience in the formation of thought. This study also engages with gesture theories from the perspective of McNeill (2005), Cienki and Müller (2008), Avelar (2013; 2016; 2017), and with film theories by Elsaesser and Hagener (2018) and Bordwell and Thompson (2013), as well as Mauss’s (2003) reflections on bodily techniques, in order to explore gestures in cinema not merely as visual reinforcements of speech but as elements capable of conveying and constructing metaphorical meanings independently or in complement to verbal language. The analysis focuses on the film Boi de Lágrimas, by Frederico Machado, seeking to identify and interpret multimodal metaphors that emerge from the characters’ gestures and their relation to the visual resources of the mise-en-scène. The objective is to understand how bodily expressions, in interaction with framing, structure conceptual dualities such as oppression vs. resistance and silencing vs. manifestation, revealing gesture as a political and social sign. By highlighting the expressive power of cinematic language beyond the spoken word, this research contributes to the understanding of cinema as an integrated multimodal system, in which the articulation between gesture, body, and the spectator’s cognition intensifies the film’s political critique.